Relation of serum aluminum level to uremic pruritus in end-stage renal disease patients on maintenance hemodialysis - Iman Ibrahim Sarhan; Ahmed Mohamed Tawfik; Tamer Wahid El Said; Mahmoud Nady Abd El Aziz Abd El Azim; Hussein Sayed Hussein (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Uremic pruritus is a common discomfort in end-stage renal disease patients on long-term hemodialysis. It negatively affects patients' quality of life and is associated with increased mortality. The pathogenesis of uremic pruritus is complex. Aluminum is a toxic metal and common human allergen that causes an immune reaction in patients on hemodialysis. Aluminum is hypothesized to play a vital role in the pathogenesis of uremic pruritus. Controlling serum aluminum levels is still critical for patients on long-term hemodialysis. Objectives: To determine the prevalence of hyperaluminemia and assess its correlation with uremic pruritus in patients on long-term hemodialysis. Patients and Methods: We conducted a case-control study on 90 patients on long-term hemodialysis at the dialysis units of Ain Shams university hospitals. We used the 5-D itch scale numerical rating system to determine the presence and severity of pruritus in our study participants. We collected blood samples to estimate blood urea nitrogen levels pre- and post-dialysis, as well as the measured urea reduction ratio, serum creatinine, hemoglobin level, intact parathyroid hormone, ionized calcium, serum phosphate levels, iron study and serum aluminum levels. Results: Our study showed no statistically significant differences between the pruritic and non-pruritic study groups (median values 9.78 [6.48-11.72] and 9.13 [6.3-10.4] for the pruritic and non-pruritic groups, respectively; P = 0.32). Conclusion: The serum aluminum levels of our study participants were higher than the normal levels in humans. Patients in the pruritic group had higher levels than those in the non-pruritic group. However, aluminum levels were not significantly associated with either the presence or severity of pruritus in patients on long-term hemodialysis.